PENGARUH REWARD TERHADAP MOTIVASI BELAJAR SISWA - Sarita Cyntia Aljena; Kadek Dewi Wahyuni Andari; Kartini Kartini (Universitas Borneo Tarakan, 2020)
The study is aimed to determine the effect of giving rewards to motivate students of class V at 033 elementary school in Tarakan. The research is conducted on the date of January 27th until February 24th 2020 at 033 elementray school in Tarakan. The population in this study were all fifth grade students at 033 elementary school in Tarakan. Sample research is numbered 108th students were taken to the tehnique of sampling saturated taking samples when all members of the population used as a sample. Mechanical collection of data in the study is using questionnaires, interviews are not structured, documentation and technical analysis of the data used is analysis of regression linear simple with the help of program software SPSS 21.0 for windows. The results of the analysis of the research data showed that there was a significant influence between giving rewards to students’ learning motivation in grade V 033 elementray school in Tarakan with a regression equation equation Y= 27,429 + 0.7 04 X. Where the significance of the effect was shown by fcount 48.326 ftable 3.93. While through the T test obtained the value tcount 6.954 ttable 1.982. It is shows that there are significant between giving a reward to the motivation to learn student class V at 033 elementary school in Tarakan. From the results of the test hypotheses obtained rcount 0.560 rTable 0.187. Shows that the magnitude of the effect of giving reward to the motivation to learn the student is at 31,3%, while the remaining 68,7% are influenced by variables other.